2010
DOI: 10.4049/jimmunol.1001486
|View full text |Cite
|
Sign up to set email alerts
|

Primed Antigen-Specific CD4+ T Cells Are Required for NK Cell Activation In Vivo upon Leishmania major Infection

Abstract: The ability of NK cells to rapidly produce IFN-γ is an important innate mechanism of resistance to many pathogens including Leishmania major. Molecular and cellular components involved in NK cell activation in vivo are still poorly defined, although a central role for dendritic cells has been described. In this study, we demonstrate that Ag-specific CD4+ T cells are required to initiate NK cell activation early on in draining lymph nodes of L. major-infected mice. We show that early IFN-γ secretion by NK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 60 publications
6
87
0
1
Order By: Relevance
“…22,24,25 Infection and tumor models in mice also showed that antigen-specific CD4 C T cells were required for the early IFNg induction from NK cells. 23,26,28 Our previous study revealed that CD4 C T cells were indispensable for maintaining potent effector function of adoptively transferred preactivated NK cells in total-body irradiated tumor-bearing mice. 9 To address whether CD4 C T cell help to NK cells can occur in absence of specific tumor antigens, tumor-derived factors and irradiation, we co-transferred CD4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,24,25 Infection and tumor models in mice also showed that antigen-specific CD4 C T cells were required for the early IFNg induction from NK cells. 23,26,28 Our previous study revealed that CD4 C T cells were indispensable for maintaining potent effector function of adoptively transferred preactivated NK cells in total-body irradiated tumor-bearing mice. 9 To address whether CD4 C T cell help to NK cells can occur in absence of specific tumor antigens, tumor-derived factors and irradiation, we co-transferred CD4…”
Section: Discussionmentioning
confidence: 99%
“…9,[22][23][24][25][26][27][28] Regulatory T cells were reported to restrain IL-2 dependent CD4 C T cell help for NK cell proliferation and activity. [29][30][31] Our previous study demonstrated that adoptive transfer of IL-12/15/18-pretreated NK cells into irradiated tumor-bearing mice resulted in antitumor activity that required the presence of host CD4 C T cells and IL-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is also noteworthy that the FV-specific priming and reactivation of CD4 ϩ T cells were not severely affected in B cell-deficient mice (27). Further, activation of both CD8 ϩ effecter T cells and NK cells upon pathogen invasion are known to depend on CD4 ϩ T cells, as CD4 ϩ T cells are required for the induction of CD8 ϩ effector cells (1,4,48,53) and NK cell activation upon pathogen infection is shown to be induced in the presence of CD4 ϩ effector T cells (6,22). In addition, CD4 ϩ T cells themselves may act as cytotoxic effector cells in eliminating FV-infected target cells (24).…”
Section: Cd4 -B -Wtmentioning
confidence: 99%
“…Target cells initiate NK cell activation if they express sufficient amounts of ligands for activating NK cell receptors and low levels of ligands that engage inhibitory receptors [6]. In addition, NK cell priming with DCs [18], their interaction with CD4 + T cells ( [19] and our unpublished observations) or neutrophils [20,21] or the presence of certain cytokines, such as IL-2, IL-12, IL-15, IL-18 or IL-21 [22], can further enhance their effector function.…”
Section: Introductionmentioning
confidence: 99%